District Health Service Management - Poudel, SK; Subedi, S; Khadka, S; Timilsina, S; Sharma, S; Roy, SK; Gaire, S; Poudel, S; Shrestha, S; Jha, V; Yadav, V; Thapa, Y (Journal of Gandaki Medical College-Nepal, 2019)
District Health System Management is a comprehensive study of the health system of the district as a unit of national health system. The report of District Health System Management has been prepared as per the MBBS 4th year (Third phase) curriculum of Tribhuvan University (TU), Institute of Medicine (IOM), Nepal after the field placement of our group in Gorkha and Kaski districts. We prepared regional health directorate profile, regional tuberculosis center profile, district profile, district health profile of Kaski, hospital profile of Western Regional Hospital, Kaski, and critical analysis on human resources of the Aampipal hospital. We prepared five year plan on ICU services of Gorkha District Hospital and conducted epidemiological study on COPD in WRH, Pokhara. The techniques used in this study were observation, interviews, interactions, participation, secondary data retrieval, analysis and presentation using specific tools and guidelines devised for the same. The field practice proved to be a milestone in enabling the students to develop aptitude in the fields of management, administration and communication in different health set-ups of the country. It is in fact once-in-a lifetime opportunity for the medical students to imbibe the practicality of management skills at various levels.